2019
DOI: 10.1001/jamainternmed.2018.6226
|View full text |Cite|
|
Sign up to set email alerts
|

Association of 30-Day Mortality With Oral Step-Down vs Continued Intravenous Therapy in Patients Hospitalized With Enterobacteriaceae Bacteremia

Abstract: IMPORTANCE Conversion to oral therapy for Enterobacteriaceae bacteremia has the potential to improve the quality of life of patients by improving mobility, eliminating catheterassociated discomfort, decreasing the risk for noninfectious and infectious catheterassociated adverse events, and decreasing health care costs. OBJECTIVE To compare the association of 30-day mortality with early oral step-down therapy vs continued parenteral therapy for the treatment of Enterobacteriaceae bloodstream infections. DESIGN,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 24 publications
7
81
0
4
Order By: Relevance
“…A recent observational study by Tamma et al showed similar 30-day mortality in a cohort of hospitalized patients with Enterobacteriacea bacteremia who received oral step down therapy compared to ongoing intravenous therapy [19]. Nearly half the patients in their study were male.…”
Section: Discussionmentioning
confidence: 89%
“…A recent observational study by Tamma et al showed similar 30-day mortality in a cohort of hospitalized patients with Enterobacteriacea bacteremia who received oral step down therapy compared to ongoing intravenous therapy [19]. Nearly half the patients in their study were male.…”
Section: Discussionmentioning
confidence: 89%
“…The literature for gram-negative BSI has significantly changed treatment recommendations by supporting shorter treatment durations [ 28 ], early switch to oral antibiotics [ 29 ], and demonstrating lack of benefit of repeat blood cultures [ 30 ]. Using an approach that is well described in gram-positive infections, Erickson and colleagues conducted a single-center, retrospective cohort evaluation of an antimicrobial stewardship bundle coupled with rapid diagnostic tests (RDTs) for uncomplicated gram-negative bacteremia [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…They found that both oral step-down therapy and early de-escalation of therapy were not associated with higher 30-day mortality rates and clinical fail-ure rates in BSIs with Enterobacteriaceae. Furthermore, switch to oral therapy shortened the duration of hospitalization significantly (65,66).…”
Section: Early Prediction Methods For Bloodstream Infections With Esbmentioning
confidence: 99%